An Investigation on Practical Synthesis of Carboxylic Acid Derivatives Using p-Toluenesulfonyl Chloride - Eskandari, Parvin; Kazemi, Foad (Letters in Organic Chemistry, 2017)
Background: Carboxylic acid derivatives are well recognized as important class of reagents frequently used in the preparation of a variety of fine or special chemicals such as amides, esters, peptides, drugs, and dyes. Although several methods were developed for the preparation of these compounds, many of them present difficulties, including low yield, high reaction temperature, harsh reaction conditions, tedious work-up, and incompatibility with scale-up. Methods: The synthesis of carboxylic anhydrides is developed through the reaction of carboxylic acids with TsCl in the presence of K2CO3 and acetonitrile as a solvent under ultrasound irradiation and conventional conditions. In addition, one-pot synthesis of acyl azides was carried out in the presence of produced carboxylic anhydrides and the addition of sodium azide under identical condition. Results: A series of carboxylic anhydrides and acyl azides were synthesized using TsCl under ultrasound irradiation and conventional stirring with simple procedure, mild reaction conditions, high yields, and scale-up ability without any restriction. In most cases, the reaction under ultrasound irradiation was better in both yields and the reaction times compared to the conventional method. Conclusion: A convenient method has been developed for the preparation of carboxylic anhydrides and acyl azides under ultrasound irradiation and conventional stirring. The present method is practical and a highly effective alternative for previous reports. The major advantages of this method are: (i) simplicity of the procedure (ii) high yields and high purity of product (iii) scale-up capacity without considerable limitation in conventional system. Under ultrasound irradiation short reaction times as compared to conventional method are observed; yields are comparable to or better than conventional method.
Keywords: Carboxylic anhydride